Encapsulation and Release Control of Fish Pathogen Utilizing Cross-Linked Alginate Networks and Clay Nanoparticles for Use with a Potential Oral Vaccination - Su-Bin Lee; Ji-Yeon Kim; Kyusik Kim; Kyoung-Jin Ahn; Tae-il Kim; Jae-Min Oh (Applied Sciences, 2020)
Streptococcus parauberis is utilized as an oral vaccine by first inactivating the cells with formalin to produce formalin- killed cells (FKC) and then encapsulating them with polymer beads consisting of a cross-linked alginate-Ca2+ network. The encapsulation efficiency and media-dependent release are controlled by pre-treating the FKC with two types of clay nanoparticles: kaolinite (KA) and layered double hydroxide (LDH). The addition of LDH induced large agglomerates of FKC, and the KA enhanced the dispersion of FKC. The differences in the dispersibility of the FKC upon the use of clay nanoparticles was determined to strongly affect the encapsulation efficiency and release properties. The FKC + LDH mixture exhibited a slightly reduced encapsulation efficiency compared to the FKC alone. However, FKC + KA exhibited a dramatically improved encapsulation efficiency. In terms of the media-dependent release, the alginate beads were found to be fairly stable under gastric conditions and in deionized water with or without clay nanoparticles, preserving most of the encapsulated FKC. The intestine was the final target organ for FKC vaccination, and release at the site varied according to the use of clay nanoparticles. Both clays seemed to enhance the release of FKC, the cumulative amount being 3.6 times and 1.3 times larger for LDH and KA, respectively, than was shown with only FKC encapsulated beads.